Service stacking using energy storage systems for grid applications – A review. (April 2023) - Hjalmarsson, Johannes; Thomas, Karin; Boström, Cecilia
Abstract: Energy storage solutions for grid applications are becoming more common among grid owners, system operators and end-users. Storage systems are enablers of several possibilities and may provide efficient solutions to e.g., energy balancing, ancillary services as well as deferral of infrastructure investments. To ensure that an energy storage investment is guaranteed a reasonable payback period and a good return of investment it is advantageous to consider the possibility of service stacking. By offering additional services in turns or in parallel with the main service it is possible to create important revenue streams. The aim of this review is to provide an up-to-date status of service stacking using grid connected energy storage systems by presenting current research and on-the-table ideas. Results from the review show that frequency regulation services are the most common services to offer together with energy arbitrage and integration of renewable energy sources. The results also show that it is strategically favorable to offer additional services for storage units which are used seasonally or with low frequency. It can be concluded that service stacking is a promising method to implement for storage operators to increase the degree of utilization of storage units. It may also be concluded that the increased need for ancillary services increases the opportunity for storage units to participate in markets for energy and ancillary services. Future studies could focus on the correlation between service stacking possibilities and actual placement of the storage, and how hybrid storage configurations would affect the potential of service stacking. Highlights: Service stacking is a promising method to improve energy storage system integration. There are several interesting cases where service stacking is crucial. Frequency supportive services are the most common to add when expanding portfolios. There is no standard method to solve optimization of service portfolios. The method is applicable to all storage technologies throughout the power system.